Singly curved shell element for applied element method - Christy, D. Lincy; Pillai, T.M. Madhavan; Nagarajan, Praveen (Journal of Structural Engineering, 2024)
Applied Element Method (AEM) is a numerical method which conventionally uses rectangular elements for structural analysis. AEM is advantageous because of its simplicity and faster processing. AEM can be used to track the collapse of structures. This method deploys the conversion of the structure into an assembly of rigid elements and flexible springs. Basically AEM has only two elements – two dimensional element and three dimensional (3D) element. Generally, 3D element is used for the analysis of 3D curved members which consumes more memory and processing time. For this, a shell element is necessary to represent the curved nature of the structure. This paper attempts to develop a singly curved shell element for AEM. The analysis of axisymmetric member illustrates the use of shell element. The effect of Poisson’s ratio normally neglected in rigid body methods is incorporated in this simplified shell element. The element developed is validated by both static and modal analyses. The results show that AEM is effective in predicting the behaviour of singly curved structures accurately.